2012
DOI: 10.1128/aem.01778-12
|View full text |Cite
|
Sign up to set email alerts
|

Serratia marcescens Quinoprotein Glucose Dehydrogenase Activity Mediates Medium Acidification and Inhibition of Prodigiosin Production by Glucose

Abstract: ABSTRACTSerratia marcescensis a model organism for the study of secondary metabolites. The biologically active pigment prodigiosin (2-methyl-3-pentyl-6-methoxyprodiginine), like many other secondary metabolites, is inhibited by growth in glucose-rich medium. Whereas previous studies indicated that this inhibitory effect was pH dependent and did not require cyclic AMP (cAMP), there is no information on the gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
35
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 62 publications
5
35
1
Order By: Relevance
“…For example, gluconic acid is a major organic acid produced by many gram-negative bacteria during phosphate solubilization and is produced by several plant growth-promoting bacteria (PGPB) [27,42]. Our results also show that P solubilization was related to the secretion of organic acids.…”
Section: Discussionsupporting
confidence: 52%
“…For example, gluconic acid is a major organic acid produced by many gram-negative bacteria during phosphate solubilization and is produced by several plant growth-promoting bacteria (PGPB) [27,42]. Our results also show that P solubilization was related to the secretion of organic acids.…”
Section: Discussionsupporting
confidence: 52%
“…Mutation of genes involved in 3=-5=-cAMP production (cyaA) and the transcription factor that responds to cAMP (crp) confers robust phenotypes beyond catabolite repression, including increased prodigiosin production (18), elevated serratamolide pro-duction (19), increased biofilm formation through increased type I pili production (20), enhanced extracellular protease production (21), and a loss of flagellum-based motility (22). CRP similarly regulates motility, adhesion, and secondary metabolite production by such diverse bacteria as Salmonella enterica serovar Typhimurium and Streptomyces coelicolor (1)(2)(3)(4).…”
mentioning
confidence: 99%
“…S. marcescens was mutated using mariner transposon delivery vector pSC189 and mutations were mapped as previously described (Chiang and Rubin, 2002) (Fender et al, 2012). The plasmids used in the study were reported elsewhere (Shanks et al, 2009, 2013, 2012), except for pMQ262 noted below.…”
Section: Methodsmentioning
confidence: 99%